2018
DOI: 10.3390/su10103605
|View full text |Cite
|
Sign up to set email alerts
|

Roaming through the Maze of Maize in Northern Ghana. A Systems Approach to Explore the Long-Term Effects of a Food Security Intervention

Abstract: Central to food security interventions in Sub-Saharan Africa stands the value chain approach. The underlying idea is that connecting farmers to input and output markets and sources of knowledge and technology will enhance their food security status. In spite of positive impacts measured in especially food supply, there is scant evidence of the long-term effects on food security. For a better grasp of the impacts of a maize value chain intervention in North Ghana, we have experimented with an approach that focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…The 2008 global food crisis had earlier mainstreamed the importance of food security in the global policy agenda [39]. Since then, numerous efforts have been made to establish measures for understanding this multifaceted concept.…”
Section: Emerging Food Security Challenges and Assessment Methodsmentioning
confidence: 99%
“…The 2008 global food crisis had earlier mainstreamed the importance of food security in the global policy agenda [39]. Since then, numerous efforts have been made to establish measures for understanding this multifaceted concept.…”
Section: Emerging Food Security Challenges and Assessment Methodsmentioning
confidence: 99%
“…Indeed, given that smallholders are confronted with many income needs, they are sometimes likely to give priority to the present ones over future food needs [11,71]. Elsewhere, studies have indicated that a focus on production for markets risks a decline in overall food production, adversely affecting, for example, the availability of diverse food in a community [72][73][74].…”
Section: Inclusive Business and Food Security Nexusmentioning
confidence: 99%
“…In 2005 the Agricultural Production Support Programme started distributing packages of inputs, fertiliser and cash to farmers. In the late 2000s Yara and Wienco fertiliser and input companies created the Masara N'arziki programme, which organised farmer groups around the supply of loans in inputs, seeds and ploughing services in contracts in which farmers supplied agro-processing corporations with specific crops (Mangnus and van Westen 2018). The main focus of the Masara N'arziki programme has been to encourage the uptake of hybrid maize varieties and synthetic inputs by smallholder farmers.…”
Section: Changing Relations Of Productionmentioning
confidence: 99%